The metabolic syndrome is frequent in children and adolescents with type 1 diabetes compared to healthy controls. Issue 7 (1st July 2022) - Mørk, Freja Barrett; Madsen, Jens Otto Broby; Pilgaard, Kasper Ascanius; Jensen, Andreas Kryger; Klakk, Heidi; Tarp, Jakob; Bugge, Anna; Heidemann, Malene; Van Hall, Gerrit; Pociot, Flemming; Wedderkopp, Niels; Johannesen, Jesper
Abstract: Objective: There is a rise in overweight and obesity among children and adolescents with type 1 diabetes (T1D) in parallel with the rise in the metabolic syndrome (MetS) among children and adolescents. The aim of the study was to describe the prevalence and characteristics of MetS in children and adolescents with T1D compared to their healthy counterparts. Research Design and Methods: The study includes two Danish cohorts; (i) the Copenhagen cross sectional cohort 2016 of 277 children and adolescents with T1D that attend the pediatric outpatient clinic at a large hospital in greater Copenhagen and (ii) the CHAMPS‐study DK which is a population‐based cohort study of Danish children and adolescents (control cohort). Participants were categorized to have MetS if at least two of the following criteria were met: (i) systolic and/or diastolic blood pressure ≥ 90th percentile, (ii) waist circumference ≥90th percentile, and (iii) triglyceride ≥90th percentile and/or HDL ≤10th percentile. Results: The prevalence of children with Mets in the T1D cohort was higher than in the control cohort ( p = 0.002). Moreover, participants with T1D had MetS at a lower level of BMI ( p < 0.001) and waist circumference ( p < 0.001) than participants with MetS from the control cohort ( z ‐scores = 0.90 and 1.51). Participants with MetS were younger than the other T1D participants (median 12.8 [9.9, 14.8] vs. median 14.6 [11.2, 16.9] years, p = 0.006). Conclusions: Children and adolescents with T1D have an increased risk of MetS compared to healthy controls and clinicians and caretakers should consider early prevention and health promotion strategies.